A model investigation of the mechanisms of external sulfate attack on portland cement binders. (30th June 2018) - Feng, Pan; Liu, Jiaping; She, Wei; Hong, Jinxiang
Highlights: A microstructure model simulates crystallization pressure induced expansion in sulfate attack. Damage of microstructures at different depths alters the rates of sulfate ingress. Insights of sulfate attack mechanism are given. Reduction of pH of the pore solution destabilizes AFm when carbonates are present. AFm can spontaneously transform to AFt without any additional sulfate addition. Abstract: A recent microstructural model for simulating external sulfate attack on cement paste is used to calculate the driving force for local expansive growth of AFt phase in terms of crystallization pressure, and the strain and stress fields are tracked within the microstructure with micrometer-scale resolution using a linear elastic finite element model. Damage induced by expansion modifies both the local effective transport properties and linear elastic properties of each microstructure at different depths, and thereby potentially alters the rates of sulfate ingress and expansion. Simulations give insight about sulfate attack mechanisms, which are investigated in more detail by separating the individual influences of sulfate concentration and pH of the pore solution. Especially when soluble carbonates are present, reductions in the pore solution pH, which often accompany ingress of sulfates, significantly destabilizes calcium monosulfoaluminate and accelerates AFt growth. In fact, within a narrow pH range some calcium monosulfoaluminate can spontaneously transform to AFt without any additional sulfate addition. Therefore, the progress of phase transformations and expansion from the surface to the interior of the porous material is dictated by the rate of ingress of concentration fronts of both sulfate ions and pH, which do not necessarily coincide.